Territorial peace and gold mining in Colombia: local peacebuilding, bottom-up development and the defence of territories. Issue 3 (3rd May 2020) - Le Billon, Philippe; Roa-García, María Cecilia; López-Granada, Angelica Rocío
ABSTRACT: The concept of territorial peace is at the core of the peace agreement signed by the Colombian government and FARC guerrilla movement in 2016. Recognising the uneven distribution and experiences of violence across Colombia, territorial peace seeks to achieve peace and reconciliation through more inclusive citizenship and new forms of territorial development, including bottom up aspirations. Figuring prominently in official policies, the concept of territorial peace is being put to the test of implementation across regions and economic sectors. Building on studies of 'extractive territories' emphasising the emergence of territorial subjects and governable spaces of mineral extraction, we examine the case of gold mining, which saw a massive boom and numerous conflicts taking place around the time of peace negotiations and post-agreement transition. Whereas territorial peace called for a bottom-up and participatory approach resting on local communities and artisanal mining livelihoods, we find that the state turned to a top-down governance strategy mobilising alienating forms of formalisation, criminalisation and industrialisation. By exacerbating community marginalisation, social tensions, human rights abuses, and inequalities, we suggest that this strategy not only undermined some of the principles of a territorial peace, but risked perpetuating poverty, environmental degradation and various forms of violence.